Bioinspired Asymmetric Total Synthesis of Emeriones A–C. Issue 32 (28th June 2022) - Jänner, Sven; Isak, Daniel; Li, Yuli; Houk, Kendall N.; Miller, Aubry K.
Abstract: We report asymmetric bioinspired total syntheses of the fungal metabolites emeriones A–C via stereoselective oxidations of two bicyclo[4.2.0]octadiene diastereomers. The central bicyclic scaffolds are prepared in an 8π/6π electrocyclization cascade of a stereodefined pentaene, which contains the fully assembled side chains of the emeriones. The anti‐aldol side chain is made using a Paterson‐aldol addition, and the epoxide of the dioxabicyclo[3.1.0]hexane side chain via ring‐closure onto an oxidized acetal. Our work has enabled the structural revision of emerione C, and resulted in the synthesis of a "missing" family member, which we call emerione D. DFT calculations identified two methyl groups that govern torquoselectivity in the 8π/6π cascade. Abstract : The emeriones, three highly oxidized and densely functionalized polyketides, were synthesized from two enantioenriched fragments in a Stille‐8π/6π sequence, followed by late‐stage stereo‐ and chemoselective oxidations. This work enabled the structural revision of emerione C.